2013
DOI: 10.2337/db13-0627
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Directly Promotes Vascular Endothelial Insulin Transport

Abstract: Insulin resistance strongly associates with decreased nitric oxide (NO) bioavailability and endothelial dysfunction. In the vasculature, NO mediates multiple processes that affect insulin delivery, including dilating both resistance and terminal arterioles in skeletal muscle in vivo. However, whether NO directly regulates vascular endothelial cell (EC) insulin uptake and its transendothelial transport (TET) is unknown. We report in this article that l-NG-nitro-l-arginine methyl ester (l-NAME) pretreatment bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 33 publications
(82 reference statements)
3
100
0
1
Order By: Relevance
“…Nitric oxide (NO) can influence vesicle activity and re-location processes, and NO directly stimulates insulin transport in vascular endothelial cells. 39 One of our prior studies showed that LPS affects insulin transport across the BBB by modulating NOS isozyme activity. 23 NO released by endothelial NOS and inducible NOS acts to stimulate insulin transport.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) can influence vesicle activity and re-location processes, and NO directly stimulates insulin transport in vascular endothelial cells. 39 One of our prior studies showed that LPS affects insulin transport across the BBB by modulating NOS isozyme activity. 23 NO released by endothelial NOS and inducible NOS acts to stimulate insulin transport.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that insulin, through its signaling pathways in the endothelium, facilitates its own movement across the endothelial cells [15]. Very recently, we reported that eNOS and its activity play a critical role in regulation of insulin uptake and TET as inhibition of eNOS activity completely eliminates endothelial insulin uptake and TET [16]. Next critical question we would ask is how insulin intracellular signaling stimulates and coordinates the assembling of the molecular machinery for insulin trans-endothelial transport?…”
Section: Editorialmentioning
confidence: 99%
“…This process is significantly impaired in insulin resistance states such as obesity and type 2 diabetes [2,[7][8][9]. Current evidence obtained by us and others indicate that insulin TET is transcellular process and mediated by transporting caveolae that contain or associate with multiple structural and signaling molecules including the insulin receptor (IR), IGF-1receptor, caveolin-1, dynamin-2, actin filaments and eNOS [10][11][12][13][14][15][16][17][18]. Among these components, caveolae and its key structural protein caveolin-1 have been shown to serve as the center to organize the molecular transcytotic machinery mediating insulin TET [13].…”
Section: Editorialmentioning
confidence: 99%
“…Shaked et al [11] demonstrated that the NO-dependent TXNIP inhibition contributed to the protective effect of insulin against glucose-induced beta cell apoptosis. Finally, Wang et al [12] recently reported the ability of NO to stimulate transendothelial insulin transport by enhancing protein S-nitrosylation, which could be abolished by knockout of TXNIP.…”
Section: Admamentioning
confidence: 99%